ISYU KETUANAN MELAYU DI MALAYSIA - Amri Marzali (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2019)
Ketuanan Melayu” is a conception of Malay political hegemony in Malaysia. The terminology was firstly introduced by a member of Parliament of Malaysia from the United Malay National Organization, namely Dato’ Abdullah Ahmad, in a speech offered at the Institute of Intenational Affairs, Singapura, Agustus 30, 1986. The speech was originally aimed at countering the negative propaganda proposed by the Malaysian Indian and the Malaysian Chinese, who accused that the special socio-political privileges given to the indigenous Malaysian peoples in the Malaysia’s Constitution (partaicularly in article 153) and the affirmative discriminative New Economic Policy of 1971 have been a servere strategy to condemn the Indian and Chinese Malaysians. On the other hand, the Malays in Malaysia traced the idea of Malay political hegemony from the political situation in the period of Malay kingdom of Melaka in the 15th century. They considered the period of Melaka as the golden age of Malay political sovereignty in Selat Melaka. When Melaka was occupied by the Portuegese in the 16th century, and followed by the Dutch in the 17-18th centuries, the political sovereignty of the Malays in the Malaysian Peninsula was carried on by the newly subsequent Malay kingdoms, such as Johor, Kedah, Kelantan, and others. In this article, I proposed that what is now called Malay political hegemony could be compared to what was called beschikkingsrecht in Dutch language, in the colonial period of Indonesia. This terminology was introduced by an adat law scholar, van Vollenhoven, in 1905, referring to the sovereignty of the native peoples in Malay Archipelago over their land and political state. Lastly I find the debate on the Malay political hegemony in Malaysia recently, whether between the natives versus the immigrants, or between the ruling Malays versus the opposition Malays, are pertaining with 6 articles in the Constitution and Act of Malaysian Armforce of 1972. This set of rules is knownly called Wasiat Raja-raja Melayu (The Wasiat of the Malay Sultans). Therefore, I conclude, the Malay political hegemony is constitutionalized, thus it is unnecessary for the Malays to boasting it anymore. The real problems of the Malay political hegemony now in Malaysia rests on the way it has been implemented by the Malaysian government.